CONSTRUÇÃO DE UM REATOR DE PLASMA DESCARGA CORONA PARA ELIMINAÇÃO DE COMPOSTOS ORGÂNICOS VOLÁTEIS - Marina Medeiros Machado (Química Nova, 2015)
The impacts derived from the emission of volatile organic compounds (VOC) into the atmosphere can have harmful consequences for human health and the environment. In this regard, the present paper proposes the construction of a low-cost cold plasma reactor for the treatment of these compounds. Tests with the prototype were performed to confirm the efficiency for BTEX (benzene, toluene and xylene) samples. Degradation efficiency was confirmed by the gas chromatography method.